Enhancing Soft Tissue Recovery: Vacuum-Assisted Closure (VAC) Therapy and Split-Thickness Skin Grafting (STSG) in Posttraumatic Defect Management - Mohd. Altaf Mir; Jaya Jain (Key Flaps in Plastic Surgery, 2023)
This book chapter presents a case report and discussion on the combined use of vacuum-assisted closure (VAC) therapy and split-thickness skin grafting (STSG) in the management of a posttraumatic soft tissue defect involving the anterior abdominal wall, scrotum, and degloving of the penis with traumatic left orchidectomy. The case presentation describes the preoperative condition, diagnosis, and the need for wound debridement, VAC therapy, and subsequent STSG. The operative procedure involved wound debridement, application of a granulofoam dressing secured with adhesive drape, and connection to a VAC device. Two rounds of VAC therapy were performed, followed by the application of a split-thickness skin graft once adequate healthy granulation tissue had formed. The postoperative period remained uneventful, and satisfactory results were observed during follow-up examinations. The discussion section provides an overview of VAC therapy and STSG as individual techniques, highlighting their advantages in wound management and reconstructive surgery. The benefits of VAC therapy include enhanced wound healing, reduced bacterial burden, improved tissue apposition, and increased patient comfort. STSG allows for the coverage of large wounds, minimizes contracture risk, improves cosmetic outcomes, and enables early mobilization. The combination of VAC therapy and STSG offers synergistic effects, with VAC therapy preparing the wound bed for grafting and enhancing graft survival. The use of both techniques can reduce postoperative complications, such as infection, graft failure, and wound dehiscence. However, it is important to consider potential limitations and complications associated with these techniques, including infection, bleeding, graft failure, and donor site morbidity. The abstract highlights the significance of VAC therapy and STSG in wound management, particularly in complex soft tissue defects. It emphasizes the benefits and synergistic effects of using these techniques in combination, leading to improved outcomes, faster wound healing, and reduced complications. By understanding the principles and proper application of VAC therapy and STSG, surgeons can optimize wound management and achieve satisfactory results for patients with challenging soft tissue defects.